2018
DOI: 10.26687/archnet-ijar.v12i1.1315
|View full text |Cite
|
Sign up to set email alerts
|

The Riddles of Historic Urban Quarters Inscription on the Unesco World Heritage List

Abstract: Keywords Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The introduction of instruments conceived for preservation purposes, such as, above all, the inscription of cultural resources and specifically tangible assets (buildings, monuments, or ancient town centers) in the UNESCO World Heritage List (WHL) are currently stimulating the international debate. Many articles have questioned whether the designation in fact represents a real advantage or is rather, a burden for destinations, what its concrete effects are in terms of tourism increases, and whether that increase is consistent or compatible with the general sustainability goals of the destinations and their local communities [62][63][64][65][66][67][68]. Based on the limitations of current WHL role formulation (undermined credibility due to unbalance in the assets' geographical distribution, an excessive number of designations, difficult management of serial and transboundary resources, the limited control and sanction powers of UNESCO, poor financial resources for the protection of too many sites), and the lack of quantification regarding changes in actual tourist numbers, it is concluded that it is at least a mixed blessing, or in simple terms, a double-edged sword.…”
Section: Approaches For the Evaluation Of Sustainable Tourism In The mentioning
confidence: 99%
“…The introduction of instruments conceived for preservation purposes, such as, above all, the inscription of cultural resources and specifically tangible assets (buildings, monuments, or ancient town centers) in the UNESCO World Heritage List (WHL) are currently stimulating the international debate. Many articles have questioned whether the designation in fact represents a real advantage or is rather, a burden for destinations, what its concrete effects are in terms of tourism increases, and whether that increase is consistent or compatible with the general sustainability goals of the destinations and their local communities [62][63][64][65][66][67][68]. Based on the limitations of current WHL role formulation (undermined credibility due to unbalance in the assets' geographical distribution, an excessive number of designations, difficult management of serial and transboundary resources, the limited control and sanction powers of UNESCO, poor financial resources for the protection of too many sites), and the lack of quantification regarding changes in actual tourist numbers, it is concluded that it is at least a mixed blessing, or in simple terms, a double-edged sword.…”
Section: Approaches For the Evaluation Of Sustainable Tourism In The mentioning
confidence: 99%
“…This image can be interpreted from the perspective of residents, domestic, and foreign. Some studies emphasize on the role of city image as the significant determinants of visit intentions (Shirvani Dastgerdi & De Luca, 2018a) and tourist destination marketers' invest a great amount of resources to create a favorable and desirable image, which conquers potential travelers to visit or re-visit their destination (Martins, 2015;Shirvani Dastgerdi & De Luca, 2018b). However, understanding residents' perceptions of tourism impacts and their level of support for its development is considered vital for the boosting city image (Stylidis, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The applications of the A'WOT method are varied and cover as major fields natural resource management [32,[35][36][37], sustainable tourism and tourism management [25,34,38,39], strategic assessment and group decision making (see among others, [40][41][42][43]). Although in the field of cultural heritage assessment, there are a flourishing set of recent contributions in literature on the sole application of AHP [44][45][46][47][48][49][50][51] and SWOT analysis [52][53][54][55][56], respectively. Nonetheless, to our knowledge, there are no contributions on the application of A'WOT to strategic decisions on cultural heritage.…”
Section: Methodological Frameworkmentioning
confidence: 99%